Diagnostic and Therapeutic Role of Combined Hysterolaparoscopy in Female Infertility (Journal of Pharmaceutical Negative Results, 2022)
Objective: We designed this study to evaluate the role of combined hysterolaparoscopy in female infertility and the incidence ofvarious pathological conditions in the female reproductive tract leadingto infertility.Materials & Methods: We conducted this prospective observational study in BLDE(DU) Shri B M Patil Medical College andResearch Centre, Vijayapur hospital from the year 2019 to 2021. Complete information regarding baseline endocrinal investigations,ovulation study, postmenstrual HSG, and semen analysis of husbands was collected. Under general anaesthesia DiagnosticHysterolaparoscopy was performed, for examining the Uterine civity pathology, 0.9% normal saline was used to dilate the uterinecavity. Meanwhile, laparoscopy was performed and chromo perturbation done to assess the tubal patency. Both Hysteroscopic andLaparoscopic findings and procedures performed were noted.Results: The major reason in the overall study group was ovarian factors (12 cases 24% ratio) while no pathology was found in 16(33%) cases. The tubal blockage was reported in 9 (18.5%) while uterine factors affected 8 (16.5%) cases (Table 2). In the primaryinfertility group 18 (53.8%) cases show normal laparoscopy results, 11(29.4%) had PCOS, and 1 (3.8%) had peritubular adhesions.Comparatively, the secondary infertility group revealed normal laparoscopy results in 4 (31.8%) cases, 2 (4.5%) PCOS cases, 5(40.9%) tubal blockage, and 3(13.6%) cases of PID. Hysteroscopic findings revealed 12 (7.6%) cases of fibroids, 4 (2.5%) cases ofpolyps, and 2 (1.2%) cases of cervical stenosis whereas 4 (9%) cases of synechiae, 2 cases of fibroids, 2 cases of polyps and 2 casesof the foreign body observed in secondary infertility group.Conclusion: In the end, we observed positive outcomes of hysterolaparoscopy in diagnosing structural abnormalities in infertilepatients.